Pengaruh Customer Experience dan Konten Media Sosial Terhadap Customer Loyalty Pada Produk Skincare GladGlow Pada Mahasiswa S1 Manajemen Universitas Dharma Andalas - Annisa Mardhatillah; Alvin Alfian (Journal of Business Economics and Management | E-ISSN : 3063-8968, 2025)
This study aims to examine and analyze the influence of Customer Experience and Social Media Content on Customer Loyalty toward Glad2Glow skincare products. The method used is descriptive quantitative. The population in this study consists of undergraduate students in the Management Program at the Faculty of Economics and Business, Dharma Andalas University. The sample size is 203 respondents, obtained using purposive sampling techniques. Data analysis was conducted using IBM SPSS 25 software through validity and reliability tests, classical assumption tests, multiple linear regression analysis, t-tests (partial), F-tests (simultaneous), and the coefficient of determination (Adjusted R²). The results of the study indicate that Customer Experience has a positive and significant effect on Customer Loyalty, while Social Media Content does not have a significant effect on Customer Loyalty. However, simultaneously, Customer Experience and Social Media Content have a significant effect on Customer Loyalty.